Hegel, la herida - Ezquerra Gómez, Jesús (Contrastes. Revista Internacional de Filosofía, 2017)
RESUMEN: La herida es el lógos, es decir, la identidad/diferencia entre algo y lo que ese algo es. El “entre”. Esa relación (identidad/diferencia) separa en la misma medida que une y une en la misma medida que separa. Por eso escribe Hegel que “el conocer cura la herida que él mismo es” (Erkennen heilt die Wunde, die es selber ist). El silogismo en Hegel es el intento de restañar con el lógos la herida que el lógos es. Este ensayo también muestra cómo la concepción hegeliana del silogismo es anticipada por el “el más bello de los enlaces” (desmôn kállistos) del Timeo platónico y por el esquematismo kantiano. PALABRAS CLAVE: HEGEL, HERIDA, SILOGISMO, IDENTIDAD/DIFERENCIA, ESQUEMATISMO ABSTRACT: The logos could be regarded as a wound. The logos is the identity/difference between something and what this something is. The “between” itself. Such relation (identity/difference) separates to the same extent it unites, and it unites to the same extent it separates. For that reason Hegel writes: “Knowledge heals the wound that it itself is” (Erkennen heilt die Wunde, die es selber ist). The syllogism in Hegel is the attempt to stanch by means of the logos the wound that the logos itself is. This paper also shows how Hegel’s concept of syllogism was previously suggested by the “fairest of all bonds” (desmôn kállistos) in the platonic Timeo and by Kantian schematism. KEYWORDS: HEGEL, WOUND, SYLLOGISM, IDENTITY/DIFFERENCE, SCHEMATISM